Research on the social function of Kazakh Folk Dance in the process of spatial transformation (On the basis of Dachaigu village of Barkol Kazakh Autonomous District) (Journal of history, 2021)
The article tells that the dance art of the Kazakh people is a centuriesold folk tradition and its social significance. It also provides information that dance forms have undergone spatial changes as a result of the transition from a nomadic lifestyle to a sedentary one. Scientific discussion of the national dance art is extremely rare. Kazakhs living in the Barkul Kazakh Autonomy still preserve the art of dance. Kazakhs are the older ethnic tribes in China and they have a long history of folk dances. Traditional Kazakh folk dances have different types of dances, which are characterized by the cultural life of pastoral livestock. Types of dance have not only social significance, but also information about the life and habitat of the population. It also plays an important role in describing relationships between people. Currently, due to unprecedented changes in the traditional social space in the process of resettlement of herders, there is a change in the traditional dance culture of the Kazakh ethnic group. Today, in the sociocultural space of the Kazakh people, traditional folk dance has lost its former social status, but it is playing its role in a new form.Key words: Kazakh folk dance, spatial change, social function, nomadic life, settlement.